Analysis of COVID-19 cases and sociodemographic data in the mesoregions of the state of Pará (Research, Society and Development, 2021)
Introduction: The COVID-19 pandemic, caused by SARS-CoV-2, causes everything from asymptomatic infections to severe acute respiratory syndrome, which can sometimes be fatal, requiring coping. Objective: To analyze the epidemiology of COVID-19 in the six mesoregions of the state of Pará, correlating it with the Average Human Development Index (HDIm) and the percentage of sewage treatment in the state. Methods: This is a cross-sectional descriptive study with a quantitative approach, carried out by collecting secondary data from the cases of COVID-19, collected from March 7 to May 30, 2020, and socio-demographic data from the six mesoregions. of the state of Pará. Results: 267,700 confirmed cases of COVID-19 were reported throughout the state of Pará. The mesoregions of the Southeast of Pará and the Metropolitan Region of Belém, presented the highest values, with 81,556 and 71,117, respectively. There was no difference in the number of cases between genders, however the two age groups most affected by the infection are between 30 and 39 years old (64,138 cases) and 40 to 49 years old (51,535 cases). Among the most prevalent comorbidities are Heart Diseases and Diabetes. Conclusion: The highest incidence rates of COVID-19 are concentrated in mesoregions with a large flow of people, with a tendency for sociodemographic aspects to be related to the epidemiology of COVID-19 in mesoregions of the state of Pará.